2021
DOI: 10.1186/s13046-021-01989-5
|View full text |Cite
|
Sign up to set email alerts
|

Targeting WD repeat domain 5 enhances chemosensitivity and inhibits proliferation and programmed death-ligand 1 expression in bladder cancer

Abstract: Background Chemotherapy and/or immunotherapy are first-line treatments for advanced muscle-invasive bladder cancer (BCa), but the unsatisfactory objective response rate to these treatments yields poor 5-year patient survival. Discovery of therapeutic targets essential for BCa maintenance is critical to improve therapy response in clinic. This study evaluated the role of targeting WD repeat domain 5 (WDR5) with the small molecule compound OICR-9429 and whether it could be used to treat bladder c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 52 publications
(64 reference statements)
0
43
0
Order By: Relevance
“…Nonetheless, because H3K4me3 is widely posited to be the mechanistic focal point of WDR5 function—and thus of WDR5 inhibitors; e.g. 22 , 33 39 )—and to attempt to understand the extensive transcriptomic impact of WDR5 depletion—we next asked whether mRNA changes caused by loss of WDR5 correlate with changes in H3K4me3 status.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, because H3K4me3 is widely posited to be the mechanistic focal point of WDR5 function—and thus of WDR5 inhibitors; e.g. 22 , 33 39 )—and to attempt to understand the extensive transcriptomic impact of WDR5 depletion—we next asked whether mRNA changes caused by loss of WDR5 correlate with changes in H3K4me3 status.…”
Section: Resultsmentioning
confidence: 99%
“…And WDR5 is no exception. RNAi-mediated knockdown is often used to predict whether WIN site inhibitors will have activity in specific contexts, and changes in H3K4 methylation almost always assumed to drive the molecular mechanism of response 6 , 7 , 17 22 . But knockdown studies conflate blocking the WIN site of WDR5 with loss of the entire protein, and because WDR5 is pan-essential 23 cannot explain how WIN site inhibitors show cancer cell-selective inhibition in vitro 6 , 11 , 17 .…”
Section: Introductionmentioning
confidence: 99%
“…There are more and more studies on the regulation of PD-L1 in BC. For example, recent studies have shown that WDR5 activates PD-L1 expression through H3K4me3 modification, and OICR-9429 targets WDR5 to inhibit immune escape by blocking PD-L1 ( 42 ). PD-L1 has been shown to weaken the antitumor immune response and plays an important role in a variety of tumors ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies found that WDR5 activates PD-L1 expression through H3K4me3 modification, and OICR-9429 targets WDR5 to inhibit immune evasion by blocking PD-L1. 50 In this study, we evaluated the predictive value of AI-score in predicting immunotherapy benefit and immune response in anti-PD For personal use only.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies found that WDR5 activates PD-L1 expression through H3K4me3 modification, and OICR-9429 targets WDR5 to inhibit immune evasion by blocking PD-L1. 50 In this study, we evaluated the predictive value of AI-score in predicting immunotherapy benefit and immune response in anti-PD-1/PD-L1 immunotherapy cohorts. We observed significant differences in the clinical benefit of immunotherapies targeting PD-1 and/or CTLA4 in the high and low AI-score subgroup.…”
Section: Discussionmentioning
confidence: 99%